2020
DOI: 10.3389/fmicb.2020.575041
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of (p)ppGpp Reveals Its Versatile Binding Pattern for Diverse Types of Target Proteins

Abstract: Kushwaha et al. Structural Analysis of (p)ppGpp Nucleotides that guanine base-specific contacts are key determinants to discriminate functional class of protein. Altogether, our studies provide significant information to understand the differential interaction pattern of (p)ppGpp to its target and this information may be useful to design antibacterial compounds based on (p)ppGpp analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Accordingly, aligning 26 (p)ppGpp molecules by their guanine ring and ribose reveals a veritable tree-like diversity in the conformations of the phosphate arms (Figure 4c). These observations were recently supported by molecular dynamics analyses, which suggested that the two linear arms of (p)ppGpp make it much more flexible than other signaling nucleotides (50). (p)ppGpp's ability to interact with a diversity of proteins in such diverse conformations tells us that there is likely much more to learn about its breadth of interaction partners.…”
Section: (P)ppgpp Adopts Flexible Conformations In Binding Diverse Po...mentioning
confidence: 91%
“…Accordingly, aligning 26 (p)ppGpp molecules by their guanine ring and ribose reveals a veritable tree-like diversity in the conformations of the phosphate arms (Figure 4c). These observations were recently supported by molecular dynamics analyses, which suggested that the two linear arms of (p)ppGpp make it much more flexible than other signaling nucleotides (50). (p)ppGpp's ability to interact with a diversity of proteins in such diverse conformations tells us that there is likely much more to learn about its breadth of interaction partners.…”
Section: (P)ppgpp Adopts Flexible Conformations In Binding Diverse Po...mentioning
confidence: 91%
“…Collectively, these changes result in a slowdown of cell growth [Pacios et al, 2020]. The set of identified targets affected by (p)ppGpp continues to expand [Kushwaha et al, 2020]. For instance, the interaction of (p)ppGpp with the translation initiation factor IF2 halts protein synthesis [Diez et al, 2020], the suppression of GTPase activity by (p)ppGpp leads to a reduction in the number of mature ribosomes [Corrigan et al, 2016], and (p)ppGpp interaction with HPRT inhibits purine metabolism [Anderson et al, 2019].…”
Section: (P)ppgpp Alarmonesmentioning
confidence: 99%